Determinants of CERDIK Behavior and Their Impact on Medication Adherence among Hypertensive Patients: A Community-Based Study in Badung, Bali - I Putu Agus Arsana; I Gede Sathya Agastya; Yohana Virda Eka Setiawati; Arten Romario Aragae; I Putu Sejiwan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Hypertension is a non-communicable disease with the most prevalence in the world. In Pelaga Village and Belok Village, 81,92% of the 100% target for hypertension patients undergo regular treatment. In relevance to actualize SDGs goal 3 (good health and well-being), the government program "CERDIK" is carried out as an effort to control and prevent hypertension to increase compliance with taking medication. This study aims to find out the most related component of the "CERDIK" behavior to medication adherence in hypertension patients In Pelaga Village and Belok Village, Badung Regency, Indonesia. This research is an analytical observational cross sectional study involving residents in Bedali Regency, who suffer from hypertension with a large sample of 130. The independent variables are regular health checks, getting rid of cigarette smoke, physical activity, balanced diet, adequate rest, and managing stress using the "CERDIK" behavior questionnaire. The medication adherence variable uses the 8-item Morisky Medication Adherence Scale (MMAS-8) questionnaire. The data obtained were subjected to bivariate analysis using Chi-square test and multivariate analysis using logistic regression with the IBM SPSS v25 application. The results of bivariate analysis found a significant relationship on physical activity, balanced diet, sufficient resting, and stress management towards medication adherence (p-value 0,002; 0,023; <0,001; and 0,025). There was a simultaneous relationship between CERDIK and medication adherence in hypertensive patients, where physical activity and sufficient rest stated as the dominant variables.